2022
DOI: 10.3390/ijerph192416460
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Inorganic Arsenic in Rice in Brazil: A Human Health Risk Assessment

Abstract: In certain populations, rice is the main source of exposure to inorganic arsenic (iAs), which is associated with cancer and non-cancer effects. Although rice is a staple food in Brazil, there have been few studies about the health risks for the Brazilian population. The objective of this study was to assess the risks of exposure to iAs from white rice and brown rice in Brazil, in terms of the carcinogenic and non-carcinogenic effects, and to propose measures to mitigate those risks. The incremental lifetime ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Rice is known to store higher levels of As than do other crops [59]. Toledo et al [60] found a high cancer risk There are no guidelines for the acceptable risk related to carcinogenic contaminants in food. However, if we considered the acceptable risk level suggested by the WHO [58] for carcinogenic compounds in drinking water (10 −5 ), as did authors such as Shibata et al [4], the mean ILCR for rice cereal in our study would be 2.6 times higher than that level, and multi-grain cereal containing rice would be 1.3 times higher.…”
Section: Cancer Risk Of Exposure To Non-essential Elements In Infant ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Rice is known to store higher levels of As than do other crops [59]. Toledo et al [60] found a high cancer risk There are no guidelines for the acceptable risk related to carcinogenic contaminants in food. However, if we considered the acceptable risk level suggested by the WHO [58] for carcinogenic compounds in drinking water (10 −5 ), as did authors such as Shibata et al [4], the mean ILCR for rice cereal in our study would be 2.6 times higher than that level, and multi-grain cereal containing rice would be 1.3 times higher.…”
Section: Cancer Risk Of Exposure To Non-essential Elements In Infant ...mentioning
confidence: 99%
“…Rice is known to store higher levels of As than do other crops [59]. Toledo et al [60] found a high cancer risk associated with rice consumption in Brazil due to iAs exposure. In the present study, the mean ILCR for rice cereal was two times higher than that for multi-grain cereal, and approximately 12 times higher than that for non-rice-based cereal.…”
Section: Cancer Risk Of Exposure To Non-essential Elements In Infant ...mentioning
confidence: 99%